Silver-coated copper powder and preparation method thereof, conductive paste and printed RFID tag
By using thiol propionic acid self-assembled molecular layer in silver-clad copper powder to protect the defect site of bare copper defects, the problem of poor stability of silver-clad copper powder is solved, and the high stability and high conductivity of printed RFID tags under humid and heat conditions are achieved.
Patent Information
- Application Number
- CN202411874748.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The bare copper defect problem in silver-clad copper powder leads to poor stability, affecting the long-term service life and signal strength of printed RFID tags.
By growing thiopropionic acid (MPA) self-assembly molecular layer at bare copper defect sites, a dense monolayer is formed to isolate the direct contact between the copper nucleus and air, and prevent oxidation reactions.
It effectively improves the stability and conductivity of silver-clad copper powder, reduces the conductivity attenuation rate of printed RFID tags under humid and heat conditions, and extends the service life.
Smart Images

Figure CN119319248B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of conductive paste, and in particular to a silver-coated copper powder and a preparation method thereof, a conductive paste and a printed RFID tag. Background Art
[0002] Radio frequency identification (RFID) technology plays a key role in many fields such as modern logistics, warehouse management, and product traceability. The manufacturing process and performance of its core component, RFID tags, have always been the focus of industry research. Traditional RFID tags mostly rely on aluminum foil etching technology to build radio frequency antennas. This process has the defects of serious pollution, complex process, low production capacity, and high cost. Printed RFID tags abandon the complex etching process and directly print the conductive paste directly on various packaging materials, which can avoid the above problems from the root.
[0003] Printed RFID tags mainly use conductive silver paste, and its high price severely limits the application of this type of tag. Low-dimensional (and quasi-low-dimensional) conductive pastes, such as carbon nanotubes, graphene, and MXene, have certain conductivity and are relatively low in cost, but their conductivity is significantly lower than that of traditional metals, resulting in low radiation efficiency of the RF antenna made from them. It is difficult to meet the requirements of signal strength and recognition accuracy in most practical scenarios, and the application scenarios are extremely limited. Copper paste is another potential alternative material with outstanding cost advantages and high conductivity, but copper itself has active chemical properties and is easily oxidized when exposed to air, resulting in poor stability of the tags made from it, greatly reducing their service life, and also failing to meet the actual application needs of long-term stable recognition.
[0004] The emergence of silver-coated copper structure can effectively balance the contradiction between cost and stability. By wrapping the silver shell layer on the outer layer of the copper core, the excellent conductivity of silver can be used to ensure the performance of the label, and copper can be used to reduce the overall material cost. However, due to the limitations of the preparation process, the silver shell layer of the silver-coated copper powder inevitably has many coating defects, causing the copper core to be directly exposed to the air; what is more serious is that these defects will also produce a "defect effect", further accelerating the oxidation rate of the copper core, and weakening the structural stability. Although there have been some reported methods in the industry to improve the quality of silver layer coating, the cost is the introduction of higher process costs and more silver content, resulting in the final product label cost Compared with pure silver paste labels, there is no outstanding advantage. Summary of the invention
[0005] The present application provides a silver-coated copper powder and a preparation method thereof, a conductive paste and a printed RFID tag, which can solve the bare copper defect problem existing in the silver-coated copper powder at a low cost and improve the stability of the silver-coated copper powder.
[0006] In a first aspect, the present application provides a silver-coated copper powder, which comprises a copper core and a silver shell layer coated on the surface of the copper core, wherein the surface of the copper core has bare copper defect sites not coated by the silver shell layer, and the bare copper defect sites have a self-assembled molecular layer of mercaptopropionic acid.
[0007] The mercaptopropionic acid (MPA) used in this application is a short-chain self-assembling molecule whose thiol group can coordinate with metals. Thanks to the orbital structure of mercaptopropionic acid and the different reactivity of copper / silver atoms, mercaptopropionic acid can form a dense monolayer on the surface of active bare copper defect sites in a short time, but it is not easy to form an equally stable molecular monolayer on the surface of stable silver metal in the same time. The higher bond energy between mercapto and copper can ensure that the copper-based monolayer remains stable at high temperatures, and the density of the monolayer can isolate copper from air and water, prevent oxidation of the copper core, and solve the bare copper defect problem of silver-coated copper powder at a low cost, thereby producing a low-cost, high-performance printed radio frequency identification tag.
[0008] In any of the above technical solutions, the silver content of the silver-coated copper powder is 10-25wt%.
[0009] Exemplarily, the mass percentage of silver in the silver-coated copper powder is 10%, 15%, 18%, 20% or 25%.
[0010] Preferably, the silver content of the silver-coated copper powder is 10 wt %.
[0011] In any of the above technical solutions, the conductivity attenuation rate of the silver-coated copper powder is less than 20% after being left standing for 3 hours under constant temperature and humidity conditions of 80° C. and 80% humidity.
[0012] Under high temperature and high humidity conditions of double 80 (temperature 80°C, humidity 80%), the bare copper defect sites in the silver-coated copper powder will undergo oxidation reactions with oxygen, moisture and carbon dioxide in the air, causing its conductivity to decay. The present application grows and self-assembles at the bare copper defect sites to form a dense MPA monolayer, which can effectively isolate the bare copper from direct contact with the air and ensure the stability of its conductivity.
[0013] The silver content of silver-coated copper powder should be in a moderate range. Increasing the silver content helps to improve the conductivity and reduce the bare copper defect sites, but it will also increase the cost accordingly. When the silver content is too low, due to the thin silver shell, even with the protection of MPA molecules, the antenna conductivity still decays significantly under the double 80 condition. This is because the silver atoms themselves have mobility. When the silver content is too low, due to the thin silver shell, the surface silver atoms will produce additional bare copper parts as oxidation points after migration, resulting in a significant attenuation of conductivity. As the silver content increases, due to the thickening of the silver shell, the probability of the copper core being exposed to the air due to the migration of the surface silver atoms decreases, so the stability of the antenna is also improved. When the silver content is greater than 10%, the conductivity attenuation rate of the silver-coated copper powder is less than 20% after being placed under the double 80 condition for 3 hours.
[0014] In a second aspect, the present application provides a method for preparing silver-coated copper powder, characterized in that it comprises the following processes:
[0015] The method comprises the following steps: taking the initially prepared silver-coated copper powder, removing the surface oxide and mixing it with a mercaptopropionic acid solution, stirring the reaction, allowing the mercaptopropionic acid to grow on the defect sites of the bare copper to form a mercaptopropionic acid self-assembled molecular layer, separating the powder after the reaction, and washing and drying the powder; wherein the concentration of the mercaptopropionic acid solution is 0.5 to 5 mmol / L, and the reaction time is 3 to 5 hours.
[0016] Exemplarily, the concentration of the mercaptopropionic acid solution is 0.5 mmol / L, 1 mmol / L, 3 mmol / L or 5 mmol / L; and the reaction time is 3 h, 4 h or 5 h.
[0017] Preferably, the concentration of the mercaptopropionic acid solution is 1 mmol / L, and the reaction time is 3 h.
[0018] In any of the above technical solutions, the silver content of the primary silver-coated copper powder is 10-25wt%.
[0019] Exemplarily, the mass percentage of silver in the primary silver-clad copper powder is 10%, 15%, 18%, 20% or 25%.
[0020] Preferably, the silver content of the primary silver-coated copper powder is 10wt%.
[0021] In any of the above technical solutions, the solvent of the mercaptopropionic acid solution is selected from one or more of methanol, ethanol, and isopropanol.
[0022] The present application does not specifically limit the amount of the primary silver-coated copper powder and mercaptopropionic acid. It is sufficient to ensure that the primary silver-coated copper powder is fully contacted and reacted with the mercaptopropionic acid solution. It is a better choice to immerse the primary silver-coated copper powder in the mercaptopropionic acid solution. It is more appropriate to control the mercaptopropionic acid solution at 0.5-5mM. A higher concentration has little effect on the molecular assembly formation of MPA, but the cost will increase slightly; too low a concentration will reduce the self-assembly efficiency of MPA molecules. It is more appropriate to control the reaction time at 3-5 hours. Too short a time will affect the coverage integrity of the MPA molecules, and too long a time will lead to a decrease in conductivity.
[0023] In any of the above technical solutions, the particle size of the primary silver-coated copper powder is 8 to 15 microns.
[0024] Exemplarily, the initially prepared silver-coated copper powder is a silver-coated copper micro-flake powder produced by a sand-milling electrochemical plating process.
[0025] If the initial silver-coated copper powder particle size is too large, it will lead to poor slurry dispersion and cause clogging of the printing screen. If the micro-chip size is too small, it will lead to increased processing costs.
[0026] In any of the above technical solutions, methods for removing surface oxides include but are not limited to grinding, polishing, ultrasonic cleaning, pickling, electrolysis, etc.
[0027] Exemplarily, hydrochloric acid pickling is used to remove surface oxides, the hydrochloric acid concentration is 10-20%, and the pickling time is 5-10 minutes.
[0028] In any of the above technical solutions, ethanol is used for cleaning and the mixture is stirred at 100 rpm for 5 to 10 minutes to remove the dissolved and physically adsorbed mercaptopropionic acid on the surface of the powder.
[0029] In a third aspect, the present application provides a conductive paste, wherein the paste contains 65 to 85 wt % of any of the above-mentioned silver-coated copper powders.
[0030] In any of the above technical solutions, the conductive paste contains the following raw materials in the following mass ratio: 65-85% silver-coated copper powder, 5-15% resin binder, 5-15% diluent, 3-5% curing agent, and 0.5-1% dispersant.
[0031] The present application has no special restrictions on the selection of resin binders, diluents, curing agents and dispersants, and the conventional components in the art can be used. Among them, the resin binder is used to load and disperse the silver-coated copper powder; the curing agent is used to accelerate the curing rate of the printed antenna; the dispersant is used to assist the slurry to be evenly dispersed and reduce the agglomeration and sedimentation of the powder. In addition, the conductive slurry of the present application can be added with other additives according to the needs of use, including but not limited to thickeners, thixotropic agents, surfactants, stabilizers, etc.
[0032] Exemplarily, the resin adhesive is polyurethane resin and / or epoxy resin.
[0033] Exemplarily, the diluent is selected from one or more of diethylene glycol butyl ether, ethylene glycol butyl ether acetate, ethylene glycol, dibutyl phthalate, and dibasic acid esters.
[0034] Exemplarily, the diluent is selected from diethylene glycol butyl ether and diethylene glycol butyl ether acetate in a mass ratio of 1:1.
[0035] Exemplarily, the curing agent is selected from anhydride curing agents and / or amine curing agents.
[0036] Exemplarily, the anhydride curing agent is methyl anhydride.
[0037] Exemplarily, the amine curing agent is at least one of ethylenediamine, diethylenetriamine, triethylenetetramine, triethanolamine, and dicyandiamide.
[0038] In any of the above technical solutions, the dispersant is 3-(trimethoxysilyl)propyl methacrylate.
[0039] It should be noted that silver-coated copper powder and curing agent need to be added in appropriate amounts in the above conductive paste. If the content of silver-coated copper powder is too low, the paste will have insufficient conductivity, while if the content is too high, the cost will be high and the rheology will be poor. If the content of curing agent is too high, the conductivity of the paste will be affected and the brittleness of the printed antenna will increase. If the content is too low, the paste will not be completely cured at low temperatures.
[0040] In a fourth aspect, the present application provides a printed RFID tag comprising a substrate, a radio frequency identification chip and a printed radio frequency antenna, wherein the printed radio frequency antenna contains any of the silver-coated copper powders described above, or the printed radio frequency antenna is made of any of the conductive pastes described above.
[0041] The present application specifically limits the selection of substrate, RFID chip and printed RFID antenna, and conventional packaging materials in the art can be selected. Exemplary substrates include but are not limited to coated paper, glass, PET, PI, TPU. The RFID chip is preferably a UHF-RFID chip. It is worth noting that the impedance of the RFID chip and the printed RFID antenna structure must be matched.
[0042] The printed RFID tag produced by the present application adopts silver-coated copper powder, which has high and stable conductivity, and the corresponding tag reading distance is large and stable, which greatly improves the service life of the silver-coated copper paste printed tag under hot and humid conditions.
[0043] In summary, this application has the following beneficial effects:
[0044] The present application proposes a low-silver silver-coated copper powder protected by mercaptopropionic acid, which utilizes the different coordination assembly activities of mercaptopropionic acid on silver and copper to assemble on the surface of its bare copper defect sites to form a dense molecular layer, effectively isolating the bare copper defect sites from direct contact with the air, inhibiting the occurrence of oxidation reactions, thereby improving the stability of the silver-coated copper powder and achieving a balance between the cost and conductive performance of printed RFID tags. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 (a), (b), and (c) are surface photographs of the conductive pastes in Example 1, Comparative Example 1, and Comparative Example 4 after standing in air at room temperature for 60 days.
[0046] Figure 2 (a) is a scanning electron microscope image of the tag antenna surface of Example 1. Figure 2 (b) is the S2p orbital 1 x-ray photoelectron spectrum of Example 1 and Comparative Example 1.
[0047] Figure 3 The conductivity attenuation of each embodiment and comparative example after double 80 treatment for 0-180 minutes.
[0048] Figure 4 This is the antenna structure used in the printed RFID tags in the embodiments and comparative examples of the present application.
[0049] Figure 5 (a), (b), and (c) are the reading distances of the tags of Example 1, Comparative Example 1, and Comparative Example 2 after processing, 30 minutes after double 80 treatment, and 3 hours after double 80 treatment, respectively. DETAILED DESCRIPTION
[0050] Embodiments Embodiment 1, a printed RFID tag is prepared according to the following steps:
[0051] Preparation of Silver-coated Copper Powder
[0052] S1. Place 100g of sand-ground electrochemical plating silver-coated copper micro-flake powder (particle size 8-15 microns, silver content 10wt%) in 500mL 10% hydrochloric acid and stir at 150rpm for 5 minutes to remove the oxide on the surface of the metal powder. Stop stirring and let it stand for 5 minutes. After the powder settles, remove the hydrochloric acid solution to obtain the acid-washed powder.
[0053] S2. Add 500 mL of clean water to the acid-washed powder, stir at 150 rpm for 30 minutes, stop stirring and let stand for 5 minutes, and separate after the powder settles. Repeat the steps 2-3 times to remove the hydrochloric acid residue.
[0054] S3, add 500mL MPA ethanol solution (1mmol / L) to the washed silver-coated copper powder, and stir at 100rpm for 3 hours to allow mercaptopropionic acid to grow at the defect sites of bare copper to form a mercaptopropionic acid self-assembled molecular layer. Stop stirring and let stand for 5 minutes, remove the MPA ethanol solution after the powder is precipitated, and obtain the coated powder.
[0055] S4. Add 500 mL of ethanol solution to the coated powder and stir at 100 rpm for 5 minutes to dissolve the physically adsorbed mercaptopropionic acid molecules. Stop stirring and let stand for 5 minutes. Remove the ethanol solution after the powder is precipitated. Place the coated powder in a vacuum oven (<30 Pa, 40°C, 2 hours) for drying to obtain silver-coated copper powder.
[0056] Conductive paste preparation
[0057] S5. Mix polyurethane resin, diethylene glycol butyl ether, and diethylene glycol butyl ether acetate in a mass ratio of 2:1:1, stir and mix at 500rpm for 1 hour to obtain an organic carrier. Mix 100 grams of the above-mentioned silver-coated copper powder with 30 grams of the organic carrier for 2 hours, add 5 grams of methyl hexachloride curing agent and 1 gram of 3-(trimethoxymethylsilyl) propyl methacrylate during the mixing process to form a conductive rough slurry. The proportion of the conductive rough slurry components is: 73.5wt% silver-coated copper powder, 11% polyurethane resin, 5.5% diethylene glycol butyl ether, 5.5% diethylene glycol butyl ether acetate, 3.7% methyl hexachloride curing agent, and 0.8% 3-(trimethoxymethylsilyl) propyl methacrylate.
[0058] S6. Place the conductive crude slurry in a vacuum oven (>30Pa, 25°C, 30 minutes) to remove bubbles, pass through a three-roll grinder (32rpm, 89rpm, 250rpm), and then pass through a 350-mesh screen to form a conductive slurry.
[0059] Printed RFID label preparation
[0060] S7, use conductive paste to print the RF antenna structure on coated paper through 260 mesh screen printing (printing takes the first direction, and the RF antenna structure is designed according to the conductivity of the conductive paste and the impedance characteristics of the RFID chip), and pass through a 6MPa, 165℃ roller press. The RFID chip uses the NXP-U9 chip, which is coupled to the antenna through the flip chip method: after connecting the chip and the antenna through conductive glue (DELOMONOPOX AC268), the label processing is completed at 140℃ for 15s.
[0061] Embodiment 2 is a printed RFID tag, which differs from Embodiment 1 in that, in step S1, a silver-coated copper micro-flake powder having a silver content of 20 wt% is prepared by a sand-milled electrochemical plating process.
[0062] Embodiment 3 is a printed RFID tag, which is different from Embodiment 1 in that, in step S1, a silver-coated copper micro-flake powder having a silver content of 25 wt% is prepared by a sand-milled electrochemical plating process.
[0063] Embodiment 4, a printed RFID tag, is different from Embodiment 1 in that the raw material ratio of the conductive paste in step S5 is different:
[0064] S5. Mix epoxy bisphenol A resin, diethylene glycol butyl ether, and diethylene glycol butyl ether acetate in a mass ratio of 2:1:1, stir and mix at 500rpm for 1 hour to obtain an organic carrier. Mix 100 grams of the above-mentioned silver-coated copper powder with 37.8 grams of the organic carrier for 2 hours, add 6.1 grams of methyl anhydride curing agent and 1.5 grams of 3-(trimethoxymethylsilyl) methyl methacrylate during the mixing process to form a conductive rough slurry. The proportion of the conductive rough slurry components is: 68.8wt% silver-coated copper powder, 13% polyurethane resin, 6.5% diethylene glycol butyl ether, 6.5% diethylene glycol butyl ether acetate, 4.2% methyl anhydride curing agent, and 1.0% 3-(trimethoxymethylsilyl) methyl methacrylate.
[0065] Embodiment 5, a printed RFID tag, is different from Embodiment 1 in that the raw material ratio of the conductive paste in step S5 is different:
[0066] S5. Mix epoxy bisphenol A resin, diethylene glycol butyl ether, and diethylene glycol butyl ether acetate in a mass ratio of 2:1:1, stir and mix at 500rpm for 1 hour to obtain an organic carrier. Mix 100 grams of the above-mentioned silver-coated copper powder with 20 grams of the organic carrier for 2 hours, add 3.7 grams of methyl hexachloride curing agent and 0.6 grams of 3-(trimethoxymethylsilyl) methyl methacrylate during the mixing process to form a conductive rough slurry. The proportion of the conductive rough slurry components is: 80.5wt% silver-coated copper powder, 8.0% polyurethane resin, 4.0% diethylene glycol butyl ether, 4.0% diethylene glycol butyl ether acetate, 3% methyl hexachloride curing agent, and 0.5% 3-(trimethoxymethylsilyl) methyl methacrylate.
[0067] Embodiment 6, a printed RFID tag, is different from Embodiment 1 in that the process parameters of step S3 are different:
[0068] S3. Add 500 mL of MPA ethanol solution (3 mmol / L) to the washed silver-coated copper powder and stir at 100 rpm for 2 hours to allow mercaptopropionic acid to grow at the defect sites of bare copper to form a mercaptopropionic acid self-assembled molecular layer. Stop stirring and let stand for 5 minutes. After the powder is precipitated, remove the MPA ethanol solution to obtain a coated powder.
[0069] Embodiment 7, a printed RFID tag, is different from Embodiment 1 in that the process parameters of step S3 are different:
[0070] S3. Add 500 mL of MPA ethanol solution (0.5 mmol / L) to the washed silver-coated copper powder and stir at 100 rpm for 8 hours to allow mercaptopropionic acid to grow at the defect sites of bare copper to form a mercaptopropionic acid self-assembled molecular layer. Stop stirring and let stand for 5 minutes. After the powder is precipitated, remove the MPA ethanol solution to obtain a coated powder.
[0071] Comparative Example Comparative Example 1 is a printed RFID tag, which is different from Example 1 in that no mercaptopropionic acid self-assembled molecular layer grows on the surface. The specific operation is: after step S2, step S3 is not performed, and step S4 is performed directly. The other steps are performed in the same manner.
[0072] Comparative Example 2, a printed RFID tag, is different from Example 1 in that the growth time in step S3 is 0.5 h, as follows:
[0073] S3, add 500mL MPA ethanol solution (1mmol / L) to the washed silver-coated copper powder, and stir at 100rpm for 0.5 hours to allow mercaptopropionic acid to grow at the defect sites of bare copper to form a mercaptopropionic acid self-assembled molecular layer. Stop stirring and let stand for 5 minutes, remove the MPA ethanol solution after the powder is precipitated, and obtain the coated powder.
[0074] Comparative Example 3, a printed RFID tag, is different from Example 1 in that the growth time in step S3 is 0.5 h, as follows:
[0075] S3, add 500mL MPA ethanol solution (1mmol / L) to the washed silver-coated copper powder, and stir at 100rpm for 17 hours to allow mercaptopropionic acid to grow at the defect sites of bare copper to form a mercaptopropionic acid self-assembled molecular layer. Stop stirring and let stand for 5 minutes, remove the MPA ethanol solution after the powder is precipitated, and obtain the coated powder.
[0076] Comparative Example 4 is a printed RFID tag, which is different from Example 1 in that a commercially available low-temperature curing copper paste (Saya 2908A) is used to replace the conductive paste prepared in Example 1, and step S7 is performed to obtain the comparative example 4.
[0077] Comparative Example 5 is a printed RFID tag, which is different from Example 1 in that a commercially available low-temperature curing silver paste (TANAKA TNP RX) is used to replace the conductive paste prepared in Example 1, and step S7 is performed to obtain the result.
[0078] Performance test 1. Analysis of slurry conductivity and label cost
[0079] Conductivity test method: In step S7, the screen printing structure is changed from an antenna structure to a 1cm×1cm square structure. A 4-probe square resistance meter (DWR1C, Shanghai Instruments) is used to test the square resistance of the square printed product. The four probes are placed on the diagonal of the square and the corresponding square resistance value is read. The thickness of the printed film is measured by a film thickness meter (Shendawei Airipu SW6300-A), and the square resistance is converted into conductivity. The calculation formula is: conductivity = 1 / square resistance * film thickness.
[0080] Cost analysis method: The cost of the tag antenna is the unit price of the conductive paste (yuan / g) × the weight of the conductive paste of a single tag (g). The weight of the conductive paste of a single tag is obtained by dividing the total weight change of 10 sheets of coated paper before and after antenna printing (before drying) by 10. The tag cost is the tag antenna cost plus the chip cost. The cost of the single-piece tag substrate paper and the conductive adhesive cost are far less than 0.01 yuan and can be ignored.
[0081] Table 1. Analysis results of slurry conductivity and label cost
[0082]
[0083] Result analysis: As can be seen from Table 1, although pure silver paste (Comparative Example 5) has the best conductivity, its cost is too high and it lacks market competitiveness compared with traditional aluminum foil RFID tags. Although the copper paste (Comparative Example 4) tag has the lowest cost, its conductivity is significantly lower than that of the silver-coated copper tag (about 20 times the difference compared with the 10% silver-coated copper paste). To achieve the optimal reading distance, the tag size needs to be increased, which limits its application scenario. Compared with Examples 1 to 3, the higher the silver content, the higher the conductivity of the paste, but the cost will also be higher. The cost of the 20% and 30% silver-containing (Examples 2 and 3) tags is significantly higher than that of Example 1, but the advantage of conductivity is not obvious. In Example 4, due to the reduction of the total content of silver-coated copper, the theoretical cost has decreased, but because the total cost is dominated by the chip cost when the antenna cost is low, the decrease is not obvious, but due to the reduction of metal solid content, the conductivity has decreased slightly and the printing line width accuracy has decreased. In Example 5, due to the increase in the total content of silver-coated copper, the cost has increased, but the conductivity advantage is not obvious. The conductive phase content of Examples 6 and 7 is the same as that of Example 1, but the MPA growth concentration is changed. Since the subsequent cleaning step can wash away the MPA molecules that have not formed S / Ag bonds (see Figure 2 (b) XPS), therefore, the MPA growth of silver-coated copper depends on the number of bare copper sites rather than the MPA concentration. Therefore, the conductivity of Examples 6 and 7 is basically the same as that of Example 1. At the same time, since the cost of MPA is much lower than that of silver-coated copper powder, the MPA concentration has no effect on the label price.
[0084] Note: The current mainstream aluminum foil etching label itself costs about 0.13 to 0.14 yuan (using the same type of chip). However, since this process can only be processed on acid-resistant materials such as PET, a subsequent bonding process is required. The equipment depreciation cost, labor cost, energy cost, bonding material cost, etc. of this process are about 0.06 to 0.07 yuan in total, so its actual cost is about 0.19 to 0.21 yuan.
[0085] 2. Slurry stability analysis
[0086] Test method: Take 20 ml of slurry and place it in the air at room temperature for 60 days and observe the changes.
[0087] Result analysis: Figure 1 As shown in (a), the surface of the paste (pure copper paste) used in Comparative Example 4 is obviously green because of the oxidation reaction with oxygen, moisture and carbon dioxide in the air. Figure 1 As shown in (b), a small amount of green spots appeared on the surface of the slurry used in Comparative Example 1 (10% silver-coated copper, no MPA), because even with the protection of the silver shell, some bare copper that was not effectively coated by silver was oxidized and dissolved. Figure 1 As shown in (c), the slurry used in Example 1 did not change, and the slurries used in other examples and comparative examples did not change. The reason is that MPA forms a self-assembled protective layer on the bare copper surface not covered by silver to prevent the bare copper from oxidizing.
[0088] 3. Label stability analysis
[0089] Test method: Place the tag in a double 80 environment (Qingniu constant temperature and humidity chamber, 80°C, 80% humidity), and record the conductivity attenuation of the tag after being placed in the double 80 environment for 30 minutes, 1 hour, 2 hours, and 3 hours.
[0090] The conductivity attenuation rate is: 100%-(label conductivity after being placed in a double 80 environment) / (label conductivity before being placed in a double 80 environment)
[0091] Results analysis: see Figure 2 (a) SEM image of the 10% silver-coated copper printed antenna. The arrow indicates the void part not covered by the silver shell. Without the protection of the MPA monolayer, the uncoated bare copper can react directly with the air. Figure 2(b) is the S2p orbital X-ray photoelectron spectrum of Example 1 (10% silver-coated copper, MPA growth for 3 hours) and Comparative Example 1 (10% silver-coated copper, no MPA growth). Example 1 can be seen to have an obvious signature peak in the S2p region, while this peak does not exist in Comparative Example 1, indicating that the sulfur element in Example 1 comes from MPA and sulfur-containing pollutants in the environment. The double peak of sulfur in Example 1 originates from spin-orbit coupling, where the angular quantum number, the S2p peak with j=1 / 2 is 161.5 electron volts, and this binding energy is the standard binding energy when sulfur is coupled to metal. Since there is only one sulfur element form mentioned above in the S2p region, it is proved that MPA in the antenna exists in the form of a self-assembled monolayer.
[0092] Figure 3 The conductivity attenuation of each label in a double 80 environment is shown in Figure 1. A conductivity attenuation of 0% means that there is no change in conductivity before and after treatment, and a conductivity attenuation of 100% means that the antenna is not conductive after treatment. As can be seen from the figure, Example 1 (10% silver-coated copper, MPA treatment) has almost no conductivity attenuation (attenuation <5%) after being treated in a double 80 environment for 30 minutes, and after being placed for 3 hours, the attenuation is about 15%. In contrast, Comparative Example 1 (10% silver-coated copper, no MPA treatment) was placed in a double 80 environment for 30 minutes, and the conductivity attenuation reached 80%, and after being placed for 3 hours, the attenuation reached more than 96%. This attenuation rate is almost the same as that of the pure copper paste antenna (Example 4), indicating that when there is no MPA protection, even with silver shell protection, oxidation will still occur quickly through the defective part. As a reference, the pure silver paste antenna (Example 5) has a attenuation rate of only 5% under double 80 conditions for 180 minutes, indicating its stability under high temperature and high humidity conditions.
[0093] The relationship between MPA growth time and label stability is shown in Figure 3 The conductivity decay of Example 1 (10% silver content, MPA growth for 3 hours), Comparative Example 2 (10% silver content, MPA growth for 0.5 hours), and Comparative Example 3 (10% silver content, MPA growth for 17 hours) are shown. The conductivity decay of Comparative Example 2 under double 80 conditions was 49% and 66% after standing for 30 minutes and three hours, respectively. Although the stability is better than that of Comparative Example 1 (without MPA), the performance decay is still obvious. This is because the growth of the self-assembled monolayer is a dynamic process, and it gradually diffuses into a dense monolayer through adsorption and desorption organization. If the growth time is too short, the monolayer will not be dense enough, and the copper atoms in the defective part will still oxidize under high temperature and high humidity conditions due to the lack of MPA molecular protection. The conductivity decay of Example 1 and Comparative Example 3 is almost the same, proving that the MPA 3-hour growth is dense enough, and longer growth will not improve the stability of the label.
[0094] The relationship between the silver content of silver-clad copper and the stability of the label is shown in Figure 3The conductivity of Example 1 (10% silver-containing copper), Example 2 (20% silver-containing copper), and Example 3 (25% silver-containing copper) is attenuated. Figure 3 It can be seen that when the silver content is 10%, 20% and 25%, the conductivity decays by 15%, 14% and 10% respectively after 180 minutes of double 80 treatment. Although the stability is still improved, the change is not significant.
[0095] 4. Tag reading performance analysis
[0096] Test method: Voyantic's Tagformance Pro RFID system tests the key parameters of the tag such as forward tag power and radar reflection area in the 860MHz-960MHz range, and converts them into theoretical forward and reverse reading distances by the internal algorithm of Tagformance Pro. The minimum value between the two at each frequency point is taken as the tag reading distance at that frequency. Since the tag performance is related to the antenna-chip impedance matching, the test antenna structure design is mainly used to match the impedance characteristics of Example 1 (0.24ohm / sq square resistance, 6 micron thickness, structure as shown in Figure 1). Figure 4 As shown), this test is only comparable with embodiments / comparative examples with similar conductivity. Specific test embodiments include: Embodiment 1 (10% silver content, conductivity 7E5, MPA molecule growth for 3 hours), Comparative Example 1 (10% silver content, conductivity 6.5E5, no MPA molecule growth) and Comparative Example 2 (10% silver content, conductivity 7E5, MPA molecule growth for 0.5 hour).
[0097] Result analysis: Figure 5 (a) is the reading distance of the tags in Example 1, Comparative Example 1 and Comparative Example 2 at different frequencies (minimum forward and reverse reading distance). Since the antenna structure is the same and the material conductivity is similar, the three curves are almost the same. The reading distance of the antenna at 920MHz is about 10.5 meters, which is close to and slightly higher than the maximum reading distance of the same size aluminum foil etched antenna (generally 7 to 9 meters).
[0098] Figure 5 (b) is the reading distance / spectrum diagram of the tags of Example 1, Comparative Example 1 and Comparative Example 2 after being left to stand for 30 minutes under double 80 conditions. The reading distance curve of Example 1 has hardly changed, while the reading distance of Comparative Example 1 has dropped significantly (from 10.5 meters to about 1.5 meters). This is because the decrease in conductivity destroys the impedance matching between the antenna and the chip, reduces the antenna radiation efficiency, and causes a significant attenuation of the reading distance. The decrease in conductivity of Comparative Example 2 is not as serious as that of Comparative Example 1, but the reading distance frequency response curve has also changed, and the reading distance has also decreased to a certain extent at high frequencies.
[0099] Figure 5(c) is the reading distance / spectrum diagram of Example 1, Comparative Example 1 and Comparative Example 2 after standing for 3 hours under double 80 conditions. The reading distance of Example 1 is slightly reduced compared with that before double 80 treatment (the reading distance at 920MHz is reduced from 10.5 meters to 9.9 meters, a decrease of about 5%), while the reading distance of Comparative Example 1 is greatly reduced (the breakpoint is less than the minimum reading accuracy, and the reading distance at 920MHz is reduced from 10.5 meters to 0.3 meters, a decrease of 97%), and the reading distance of Comparative Example 2 is also greatly reduced (the reading distance at 920MHz is reduced from 10.5 meters to 2.95 meters, a decrease of about 72%). The above data clearly prove that the self-assembled molecular layer of mercaptopropionic acid can greatly improve the stability and service life of silver-coated copper paste printed labels under hot and humid conditions.
[0100] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A silver-coated copper powder, characterized in that: The invention comprises a copper core and a silver shell layer coated on the surface of the copper core, wherein the surface of the copper core has a bare copper defect site which is not coated by the silver shell layer, and the bare copper defect site has a mercaptopropionic acid self-assembled molecular layer.
2. The silver-coated copper powder according to claim 1, characterized in that: The silver content of the silver-coated copper powder is 10-25wt%.
3. The silver-coated copper powder according to claim 1, characterized in that: The silver content of the silver-coated copper powder is 10 wt %.
4. The silver-coated copper powder according to claim 1, characterized in that: The conductivity attenuation rate of the silver-coated copper powder after standing for 3 hours under constant temperature and humidity conditions of 80° C. and 80% humidity is less than 20%.
5. A method for preparing silver-coated copper powder, characterized in that: The following operations are included: The method comprises the following steps: taking the initially prepared silver-coated copper powder, removing the surface oxide and immersing the powder in a mercaptopropionic acid solution, stirring the reaction, allowing the mercaptopropionic acid to grow on the defect sites of the bare copper to form a mercaptopropionic acid self-assembled molecular layer, separating the powder after the reaction, washing and drying the powder to obtain the silver-coated copper powder; wherein the concentration of the mercaptopropionic acid solution is 0.5-5 mmol / L, and the reaction time is 3-5 hours.
6. The method according to claim 5, characterized in that The particle size of the primary silver-coated copper powder is 8 to 15 microns.
7. A conductive paste, characterized in that: The slurry contains 65-85 wt % of the silver-coated copper powder described in any one of claims 1-4 or the silver-coated copper powder prepared by the method described in any one of claims 5-6.
8. The slurry according to claim 7, characterized in that The invention comprises the following raw materials in percentage by weight: 65-85% of silver-coated copper powder, 5-15% of resin adhesive, 5-15% of diluent, 3-5% of curing agent and 0.5-1% of dispersant.
9. The slurry according to claim 8, characterized in that The dispersant is 3-(trimethoxysilyl)propyl methacrylate.
10. A printed RFID tag, characterized in that: The label comprises a substrate, a radio frequency identification chip and a printed radio frequency antenna. The printed radio frequency antenna contains the silver-coated copper powder described in any one of claims 1 to 6, or the printed radio frequency antenna is processed from the slurry described in any one of claims 7 to 9.
Citation Information
Patent Citations
Silver-coated copper powder, preparation method, application of silver-coated copper powder in silver-coated copper slurry and method for detecting compactness of silver coating layer in silver-coated copper powder
CN115805310A
Preparation method and post-processing method of silver-coated copper powder
CN116037920A